On the Inequality of Lives Inaugural Lecture delivered on Thursday 16 January 2020 - Fassin, Didier (Leçons inaugurales, 2023)
There is, on the one hand, life that flows from a beginning to an end, and, on the other hand, life that constitutes human singularity because it can be recounted. We may term them "biological life" and "biographical life". Life expectancy measures the length of the former; a life story relates the richness of the latter. Only by acknowledging both can the inequality of lives be comprehended. They should be conceived of as being both distinct and connected: distinct, because the paradox of French women shows that a long life is no guarantee of a good life; connected, because the experience of African-American men stands as a reminder that a devalued life is a damaged life. This also raises the question of refugees and migrants.